Episodic syncope in hypertrophic cardiomyopathy: evidence for inappropriate vasodilation. Issue 10 (24th July 2008) - Prasad, K; Williams, L; Campbell, R; Elliott, P M; McKenna, W J; Frenneaux, M
Abstract : Symptoms of impaired consciousness (syncope and pre-syncope) occur in 15–25% of patients with hypertrophic cardiomyopathy (HCM).1 In young patients a history of recurrent syncope is associated with an increased risk of sudden death.2 – 5 Syncope usually occurs without warning or symptoms suggestive of the cause. Detailed investigations identify a probable mechanism in a minority, usually paroxysmal atrial fibrillation or ventricular tachycardia. In the majority however no likely mechanism is found despite repeated 24-hour ambulatory echocardiography (ECG) or patient-activated monitoring, exercise testing and invasive electrophysiological studies.1 6 Empirical treatment with amiodarone, a pacemaker or an implantable cardioverter-defibrillator is commonly employed, but is often unsuccessful in relieving the symptoms. We have previously observed that approximately 30% of patients with HCM have abnormal blood pressure response during maximal upright exercise.7 8 This was due in the majority of patients to an exaggerated fall in systemic vascular resistance, possibly arising from abnormal activation of stretch-sensitive left ventricular mechanoreceptors, 9 10 by a mechanism similar to that described in aortic stenosis.11 However, in some patients an inadequate cardiac output response to exercise may be responsible.12 We hypothesised that abnormal vasodepressor-mediated hypotension may also occur during daily life in patients with HCM, and that this may be an important mechanism of syncope when conventional investigations fail to reveal a cause.